SIRT1 controls liver regeneration by regulating bile acid metabolism through farnesoid X receptor and mammalian target of rapamycin signaling. Issue 5 (31st March 2014) - García‐Rodríguez, Juan L.; Barbier‐Torres, Lucía; Fernández‐Álvarez, Sara; Gutiérrez‐de Juan, Virginia; Monte, María J.; Halilbasic, Emina; Herranz, Daniel; Álvarez, Luis; Aspichueta, Patricia; Marín, Jose J.G.; Trauner, Michael; Mato, Jose M.; et al.
<x xml:space="preserve">Abstract</x> Sirtuin1 (SIRT1) regulates central metabolic functions such as lipogenesis, protein synthesis, gluconeogenesis, and bile acid (BA) homeostasis through deacetylation. Here we describe that SIRT1 tightly controls the regenerative response of the liver. We performed partial hepatectomy (PH) to transgenic mice that overexpress SIRT1 (SIRT). SIRT mice showed increased mortality, impaired hepatocyte proliferation, BA accumulation, and profuse liver injury after surgery. The damaging phenotype in SIRT mice correlated with impaired farnesoid X receptor (FXR) activity due to persistent deacetylation and lower protein expression that led to decreased FXR‐target gene expression; small heterodimer partner (SHP), bile salt export pump (BSEP), and increased Cyp7A1. Next, we show that 24‐norUrsodeoxycholic acid (NorUDCA) attenuates SIRT protein expression, increases the acetylation of FXR and neighboring histones, restores trimethylation of H3K4 and H3K9, and increases miR34a expression, thus reestablishing BA homeostasis. Consequently, NorUDCA restored liver regeneration in SIRT mice, which showed increased survival and hepatocyte proliferation. Furthermore, a leucine‐enriched diet restored mammalian target of rapamycin (mTOR) activation, acetylation of FXR and histones, leading to an overall lower BA production through SHP‐inhibition of Cyp7A1 and higher transport (BSEP) and detoxification (Sult2a1) leading to an improved liver regeneration. Finally, we found that human hepatocellular carcinoma (HCC) samples have increased presence of SIRT1, which correlated with the absence of FXR, suggesting its oncogenic potential. Conclusion: We define SIRT1 as a key regulator of the regenerative response in the liver through posttranscriptional modifications that regulate the activity of FXR, histones, and mTOR. Moreover, our data suggest that SIRT1 contributes to liver tumorigenesis through dysregulation of BA homeostasis by persistent FXR deacetylation. (Hepatology 2014;59:1972–1983)